2022
DOI: 10.3390/ijerph19042193
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Environmental Polycyclic Aromatic Hydrocarbons (PAHs) Exposure on DNA Damage among School Children in Urban Traffic Area, Malaysia

Abstract: This study aimed to investigate the association between particulate PAHs exposure and DNA damage in Malaysian schoolchildren in heavy traffic (HT) and low traffic (LT) areas. PAH samples at eight schools were collected using a low volume sampler for 24 h and quantified using Gas Chromatography-Mass Spectrometry. Two hundred and twenty-eight buccal cells of children were assessed for DNA damage using Comet Assay. Monte-Carlo simulation was performed to determine incremental lifetime cancer risk (ILCR) and to ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 73 publications
1
2
0
Order By: Relevance
“…Since the comet assay serves as a potential cancer-predictive biomonitoring tool [23], there was a clear rationale for conducting this study. Several studies examined the impacts of high PAH exposure on children residing near heavy traffic roads or industry and noted higher blood cell comet assay descriptors compared to control populations [50][51][52][53][54], while our results align with the biomonitoring results characterizing a reference site with only occasional PM limit exceedances [55]. Some studies used salivary cells as target cells for the air pollution and did not find an increase in DNA damage in relation to air pollutants in Brescia's preschool children [56].…”
Section: Discussionsupporting
confidence: 83%
“…Since the comet assay serves as a potential cancer-predictive biomonitoring tool [23], there was a clear rationale for conducting this study. Several studies examined the impacts of high PAH exposure on children residing near heavy traffic roads or industry and noted higher blood cell comet assay descriptors compared to control populations [50][51][52][53][54], while our results align with the biomonitoring results characterizing a reference site with only occasional PM limit exceedances [55]. Some studies used salivary cells as target cells for the air pollution and did not find an increase in DNA damage in relation to air pollutants in Brescia's preschool children [56].…”
Section: Discussionsupporting
confidence: 83%
“…These studies were performed in Europe (n = 17; 36.2%), followed by Asia (n = 14; 28.8%), South America (n = 14; 28.8%), and Africa (n = 2; 4.3%). Regarding exposure to PAHs, from a total of eight (17.2%) studies, five (62.5%) were performed in children [ 129 , 131 , 135 , 154 , 156 ] and the other three (37.5%) in adults [ 133 , 150 , 158 ]. From six studies conducted in children and adolescents, two studies reported a combined exposure between PAHs, metals, and VOCs [ 149 , 160 ], and two others besides these chemical substances were also phthalates [ 73 , 139 ].…”
Section: Resultsmentioning
confidence: 99%
“…From a total of 44 studies, 35 (74.5%) performed exposure assessments; air sampling was measured in twelve (25.5%) studies, seven (14.9%) measured ambient PM, and four (8.5%) specifically quantified PAHs from PM extracts [ 127 , 135 , 140 , 156 ]. Ten (21.3%) studies measured urinary 1-OHP, an internal biomarker of PAH exposure, and 12 (25.5%) measured other metabolites in urine or blood.…”
Section: Resultsmentioning
confidence: 99%
“…The most of the people in the world did not know or reorganized that the PAHs is an organic pollutant that will destroy the environment and human health. Therefore, the anthropogenic activities implemented by humans will still release or dispose of the PAHs into the environment without considering the warning or caution given by the government [34]. Some industries did not reduce the amount of PAHs before it released or discharged to the environment.…”
Section: Future Challenges In Social Environment and Researchmentioning
confidence: 99%